Stress relaxation, creep, and recovery of carbon fiber non-crimp fabric composites - Ornaghi, Heitor L.; Almeida, José Humberto S.; Monticeli, Francisco M. [UNESP]; Neves, Roberta M. (Elsevier, 2020)
Considering that structural composites are typically composed of off-axis plies, i.e. quasi-isotropic stacking sequence, their strength and stiffness are time-dependent due to the viscoelastic character of polymer matrices. This work consists of determining creep, recovery, and stress relaxation of carbon fiber-reinforced polymer (CFRP) composites. Long-term experimental analyses are conducted via dynamic mechanical analysis under several temperatures and stress levels. From the experimental observations, the changes in the relaxation mechanisms are predicted using Fancey's latch model. The rate of relaxation at different temperatures is also covered. Since at certain strain levels the viscoelastic behavior cannot be properly determined, the stress-relaxation is determined using the time-temperature superposition (TTS) principle, considering nine temperatures at three strain levels in order to cover the three main regions of the composite system (glassy, glass transition and rubbery regions). The models and experiments herein presented can be extended to any polymeric system.
Keywords: Creep; Glass transition; Structure-property relations